GUIDE FOR AUTHORS - AGROPECUARIOS, ECISISTEMAS Y RECURSOS (Ecosistemas y Recursos Agropecuarios, 2015)
Manuscripts must be Microsoft Word, double-spaced documents, using Arial Narrow 12, and 2.5 cm margins, with consecutively numbered pages and lines. Figures and tables must be included at the end of the document. The text must be drafted in third person and passive voice. Numbers from zero to nine must be written, except if preceded by a unit, and in numerals from 10 onwards. Always use the units and abbreviations accepted by the International System of Units (see the Basic Units section).
Keywords: General guidelines; SPECIFIC FORMATS